Metabolic Status Modulates Choroidal Thickness – A Possible Early Indicator for Diabetic Eye Complications? - Meyhöfer, Svenja; Wilms, Britta; Chamorro, Rodrigo; Knaak, Armin; Pappa, Eleni; Schulz, Agnetha S.; Pagels, Anna-Josephin; Schröder, Maria; Kaluzny, Neele; Grein, Hans-Jürgen; Meyhöfer, Sebastian M. (Experimental and Clinical Endocrinology & Diabetes, 2022)
Objective To investigate the impact of metabolic status on choroidal thickness (ChT) in healthy subjects, patients with obesity, and type 2 diabetes.Design and Methods Fasting blood glucose, insulin, insulin-like growth factor-1 (IGF-1), and ChT measured by optical coherence tomography were assessed in healthy normal-weight (n=17), obese participants (n=20), and obese participants with T2D (n=16).Results ChT increased in obese participants and obese participants with T2D as compared to healthy normal-weight participants (P<0.0001). A negative correlation was observed between IGF1 and ChT (r=−0.268, P=0.050) for all cohorts. Furthermore, body mass index (BMI; R2=0.209; P=0.002; beta=0.388) and model assessment-estimated insulin resistance (HOMA-IR; R2=0.074; P=0.015; beta=0.305) were independent variables of ChT, explaining 20.9 and 7.4% of its variance (both p<0.016), whereas age, sex, and IGF-1 were not significant confounders of ChT (p>0.975).Conclusion ChT is associated with metabolic characteristics, i. e., BMI and HOMA-IR. Due to the key role of choroidal function in retinal physiology, future studies are needed to evaluate whether metabolic traits, ChT, and potential metabolic eye complications are mechanistically linked.